(untitled) (Research, Society and Development, 2025)
Introduction: Severe combined immunodeficiency (SCID) is a pathology characterized by significant impairment of the immune response involving T and/or B lymphocytes and/or NK cells, which implies increased susceptibility to infections and high mortality rates. Children with SCID are healthy at birth; infectious complications arise in the first year of life and are potentially fatal up to two years of age. Early diagnosis is essential for successful treatment, since children without infection have better clinical conditions and survival after hematopoietic stem cell transplantation (HSCT). Objectives: To report the clinical case of a patient with a late diagnosis of severe combined immunodeficiency syndrome, as well as its complications and challenges for establishing appropriate treatment. Methods: Data will be obtained through electronic and paper medical records. The study will begin after the patient’s legal guardian has completed the informed consent form, followed by approval by the Research Ethics Committee. This is an observational and descriptive study, without a control group, in the format of a clinical case report. Primary outcome/Conclusion: Its scientific relevance lies in demonstrating how delays in diagnosis and the lack of implementation of routine neonatal screening for these severe congenital pathologies result in high mortality and irreversible damage.